Gastrointestinal Tract Disorders Among In Patients at Khwaja Yunus Ali Medical College Hospital - Ali, Md Zulfikar; Iqbal, Said Mohammad; Ali, Shah Mohammad Keramat; Hossain, Bellal; Shahjahan, - (KYAMC Journal, 2017)
Gastrointestinal tract disorders are a public health problem in our country. The objective of this study was to find out hospital based information and risk factors of prevalence of the patients suffering from gastrointestinal disorders. We included all suffering from upper abdominal pain and visiting KYAMCH, A total number of 1196 patients were endoscopically examined. Among them 25.54% were found to be suffering from upper gastrointestinal tract disorders, 9.86% had erosion, 8.01% had ulcer, 3.62% had inflammation and 4.04% was found to be malignant. Duodenum Ulcer Disease among male 4% and in females 3%. The prevalence of gastrointestinal disorders in a tertiary level hospital in rural Bangladesh is increasing. KYAMC Journal Vol. 4, No.-1, July 2013, Page 316-320